American sign language syntax and analogical reasoning skills are infl uenced by early acquisition and age of entry to signing schools for th e deaf - Henner, Jon; Caldwell-Harris, Catherine L.; Novogrodsky, Rama; Hoffmeister, Robert (Frontiers in Psychology, 2016)
Failing to acquire language in early childhood because of language dep rivation is a rare and exceptional event, except in one population. De af children who grow up without access to indirect language through li stening, speech-reading, or sign language experience language deprivat ion. Studies of Deaf adults have revealed that late acquisition of sig n language is associated with lasting deficits. However, much remains unknown about language deprivation in Deaf children, allowing myths an d misunderstandings regarding sign language to flourish. To fill this gap, we examined signing ability in a large naturalistic sample of Dea f children attending schools for the Deaf where American Sign Language (ASL) is used by peers and teachers. Ability in ASL was measured usin g a syntactic judgment test and language-based analogical reasoning te st, which are two sub-tests of the ASL Assessment Inventory. The influ ence of two age-related variables were examined: whether or not ASL wa s acquired from birth in the home from one or more Deaf parents, and t he age of entry to the school for the Deaf. Note that for nonnative si gners, this latter variable is often the age of first systematic expos ure to ASL. Both of these types of age-dependent language experiences influenced subsequent signing ability. Scores on the two tasks decline d with increasing age of school entry. The influence of age of startin g school was not linear. Test scores were generally lower for Deaf chi ldren who entered the school of assessment after the age of 12. The po sitive influence of signing from birth was found for students at all a ges tested (7;6-18;5 years old) and for children of all age-of-entry g roupings. Our results reflect a continuum of outcomes which show that experience with language is a continuous variable that is sensitive to maturational age.
Keywords: Age of Acquisition; Analogies; Asl acquisition; deaf children; syntax